Anode interface layer, organic solar cell, preparation method and application

By using Dawson type heteropoly blue as the anode interface layer, the problems of low conductivity and photoelectric conversion efficiency of existing organic solar cells are solved, and significant performance improvement is achieved.

CN120152492APending Publication Date: 2025-06-13BEIJING UNIV OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510296322.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The conductivity and photoelectric conversion efficiency of existing organic solar cells are low, and Dawson type heteropoly blue is not used as the anode interface layer or the hole transport/injection layer.

Method used

The Dawson type heteropoly blue solution is coated to form the anode interface layer. The Dawson type heteropoly blue is reduced by reducing agent, which is used to improve the conductivity and photoelectric conversion efficiency of organic solar cells.

Benefits of technology

The conductivity, filling factor and photoelectric conversion efficiency of organic solar cells have been significantly improved, and the effective application of Dawson-type heteropoly blue in the anode interface layer is proved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120152492A_ABST
    Figure CN120152492A_ABST
Patent Text Reader

Abstract

The invention discloses an anode interface layer, an organic solar cell, a preparation method and application. An anode interface layer used as an organic solar cell is formed by coating a Dawson type heteropolyblue solution, and Dawson type heteropolyblue is obtained by reducing Dawson type heteropolyacid or salt thereof through a reducing agent. By adopting the anode interface layer provided by the invention, the conductivity of the formed organic solar cell can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anode interface layer, an organic solar cell, a preparation method and an application thereof. Background Art

[0002] Generally speaking, an organic solar cell (OSC) consists of an anode, an anode interface layer, an active layer, a cathode interface layer and a cathode. The anode and the cathode respectively play the role of collecting holes and electrons, the anode interface layer and the cathode interface layer respectively play the role of transporting holes and electrons, and the active layer is the main place for generating holes and electrons. The five-part structure works together.

[0003] An organic light-emitting diode (OLED) consists of an anode, a hole transport / injection layer (HTL / HIL), a light-emitting layer (EML), an electron transport / injection layer (ETL / EIL) and a cathode. The anode and the cathode respectively play the role of injecting holes (positive charges) and electrons into the device; the main role of the hole injection layer is to modify the anode surface, reduce the energy level barrier between the anode and the hole transport layer, and promote the injection of holes; the hole transport layer is responsible for transporting the holes from the anode to the light-emitting layer; the light-emitting layer is the core part of the OLED device, where electrons and holes recombine to form excitons, and the excitons de-excite to emit visible light; the electron transport layer transports the electrons from the cathode to the light-emitting layer; the main role of the electron injection layer is to modify the cathode surface, reduce the energy level barrier between the cathode and the electron transport layer, and promote the injection of electrons. These layers work together under the drive of an electric field to achieve the conversion of electrical energy to light energy.

[0004] Currently, MoO 3 is an anode interface layer widely used in organic solar cells (OSCs). For example, CN103280528A discloses a polymer solar cell, which sequentially includes: a cathode layer, a cathode interface layer, a photosensitive layer, an anode interface layer and an anode layer. In Example 1 thereof, a deposited MoO 3 layer is used as the anode interface layer. The photoelectric conversion efficiency of this solar cell is still relatively low, and the conductivity is not mentioned.

[0005] Dawson-type heteropoly blue is a type of reduced polyoxometalate. CN1623904A discloses a preparation method of heteropoly blue, which uses thiourea as a reducing agent to reduce Dawson-type heteropoly acid, and after further acidification and extraction with ether, pure two-electron heteropoly blue is obtained. Its examples list the heteropoly blue obtained by reducing heteropoly acid H 6 As 2 Mo 18 O 62 with thiourea.

[0006] CN103400941A discloses a preparation method of an organic solar cell based on a heteropolyacid anode modification layer. The heteropolyacid material is Hx[MM’ 12 O 40 , where M is P or Si, M’ is Mo or W, and x is 3 or 4. The heteropolyacid used in this method is Keggin-type heteropolyacid, not Dawson-type heteropolyacid. And the photoelectric conversion efficiency of the organic solar cell prepared by this method is relatively low.

[0007] So far, there has been no report on Dawson-type heteropolyblue as an anode interface layer or a hole transport / injection layer, and the formation of related organic solar cells, etc. Summary of the Invention

[0008] An object of the present invention is to provide an anode interface layer for an organic solar cell, and such an anode interface layer is conducive to significantly improving the conductivity of the obtained organic solar cell. Another object of the present invention is to provide a preparation method of the anode interface layer as described above. Still another object of the present invention is to provide an application of Dawson-type heteropolyblue. Yet another object of the present invention is to provide an organic solar cell formed by the anode interface layer as described above. A further object of the present invention is to provide an organic light-emitting diode formed by the anode interface layer as described above.

[0009] The present invention adopts the following technical solutions to achieve the above objects.

[0010] On the one hand, the present invention provides an anode interface layer for an organic solar cell, which is formed by coating a Dawson-type heteropolyblue solution. Among them, the Dawson-type heteropolyblue in the Dawson-type heteropolyblue solution is obtained by reducing a Dawson-type heteropolyacid or its salt with a reducing agent.

[0011] According to the anode interface layer of the present invention, preferably, the general formula of the Dawson-type heteropolyacid is Y n [X 2 M 18 O 62 ;

[0012] Among them, X is selected from one of P, As, S, Si, Cl and V, M is selected from at least one of W and Mo, n is the molar coefficient of Y, n is greater than or equal to 6 and less than or equal to 12; Y is selected from H + , Li + , Ag + , Cu + , K + , Na + , NH 4 + , Mg 2+, Ca 2+ , Sr 2+ , Co 2+ , Ni 2+ , Zn 2+ and one of organic ammonium salts.

[0013] For the anode interface layer according to the present invention, preferably, the Dawson-type heteropolyacid is selected from at least one of (Bu 4 N) 4 [W 18 O 54 (SO 3 ) 2 , (TBA) 6 [H 3 W 18 O 56 (IO 6 )] and (NH 4 ) 9 [SbW 18 O 60 (OH) 2 .

[0014] For the anode interface layer according to the present invention, preferably:

[0015] the Dawson-type heteropolyacid is selected from at least one of H 6 P 2 Mo 15 W 3 O 62 , H 6 P 2 Mo 9 W 9 O 62 and H 6 P 2 Mo 3 W 15 O 62 ;

[0016] the reducing agent is selected from one of vitamin C, glucose and thiourea.

[0017] On the other hand, the present invention also provides a method for preparing the anode interface layer as described above, comprising the following steps:

[0018] Dissolve the Dawson-type heteropolyacid in a solvent to obtain a heteropolyacid solution; mix and react the heteropolyacid solution with a reducing agent solution to obtain a Dawson-type heteropolyblue solution; coat the Dawson-type heteropolyblue solution on a substrate to form an anode interface layer.

[0019] On the other hand, the present invention also provides an application of Dawson-type heteropoly blue in forming an anode interface layer of an organic solar cell, wherein the Dawson-type heteropoly blue is obtained by reducing a Dawson-type heteropoly acid or its salt with a reducing agent; and a Dawson-type heteropoly blue solution is coated to form the anode interface layer.

[0020] On another aspect, the present invention also provides an organic solar cell, comprising an anode, an anode interface layer, an active layer, a cathode interface layer and a cathode which are arranged in sequence, wherein the anode interface layer is formed according to the anode interface layer described above.

[0021] According to the organic solar cell of the present invention, preferably, the anode is ITO, the active layer is formed by PM6 and L8-BO, the cathode interface layer is formed by PDINN, and the cathode is an Ag electrode or an Al electrode.

[0022] On another aspect, the present invention also provides an application of Dawson-type heteropoly blue in forming a hole transport / injection layer of an organic light-emitting diode, wherein the Dawson-type heteropoly blue is obtained by reducing a Dawson-type heteropoly acid or its salt with a reducing agent; and a Dawson-type heteropoly blue solution is coated to form the hole transport layer.

[0023] On yet another aspect, the present invention also provides an organic light-emitting diode, comprising an anode, a hole transport / injection layer, a light-emitting layer, an electron transport / injection layer and a cathode which are arranged in sequence; the hole transport / injection layer is formed by coating a Dawson-type heteropoly blue solution, and the Dawson-type heteropoly blue is obtained by reducing a Dawson-type heteropoly acid or its salt with a reducing agent.

[0024] The anode interface layer of the organic solar cell of the present invention is formed by coating a Dawson-type heteropoly blue solution. The conductivity of the organic solar cell composed of such an anode interface layer is significantly improved, and the fill factor and photoelectric conversion efficiency are also improved. Description of the Drawings

[0025] Figure 1 It is the infrared spectrogram of the Dawson-type heteropoly acid obtained in Preparation Example 1, Preparation Example 2 and Preparation Example 3.

[0026] Figure 2 It is the ultraviolet-visible absorption spectrogram of the Dawson-type heteropoly acid obtained in Preparation Example 1, Preparation Example 2 and Preparation Example 3.

[0027] Figure 3 It is the current-voltage curve of the organic solar cell formed by the anode interface layer of Comparative Example 1.

[0028] Figure 4The voltage-current characteristic curves of the organic solar cells formed by the anode interface layers of Comparative Example 1, Example 1, Example 2, and Example 3 under a bias voltage of 0.3V.

[0029] Figure 5 The current-voltage curve of the organic solar cell formed by the anode interface layer of Example 1.

[0030] Figure 6 The current-voltage curve of the organic solar cell formed by the anode interface layer of Example 2.

[0031] Figure 7 The current-voltage curve of the organic solar cell formed by the anode interface layer of Example 3. Detailed implementation manners

[0032] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0033] <Used as the anode interface layer of an organic solar cell>

[0034] An anode interface layer provided by the present invention is formed by coating with a Dawson-type heteropoly blue solution, wherein the heteropoly blue in the Dawson-type heteropoly blue solution is obtained by reducing a Dawson-type heteropoly acid or its salt with a reducing agent. Such an anode interface layer is beneficial to significantly improving the conductivity of the organic solar cell when forming the organic solar cell. In addition, the fill factor and photoelectric conversion efficiency of the organic solar cell are also improved.

[0035] The heteropoly blue of the present invention is Dawson-type heteropoly blue, which is obtained by a reduction reaction of Dawson-type heteropoly acid. Dawson-type heteropoly acid compounds belong to the 2:18 series and are a class of heteropoly acid compounds that have been widely studied in addition to the Keggin-type structure. The central heteroatom of the classical Dawson structure is {XO 4} in a regular tetrahedron configuration, and the ligand atoms are {MO 6} in an octahedron configuration. Two {XO 4} tetrahedrons and 18 {MO 6} octahedrons are connected by sharing edges or corners to form the classical Dawson structure.

[0036] According to one aspect of the present invention, the general formula of the Dawson-type heteropoly acid is Y n [X 2 M 18 O 62; wherein, X is selected from one of P, As, S, Si, Cl, and V, M is selected from one of W and Mo, n is the molar coefficient of Y, n is greater than or equal to 6 and less than or equal to 12; Y is selected from + H + Li + Ag + Cu + K + Na 4 + NH 2+ Mg 2+ Ca 2+ Sr 2+ Co 2+ Ni 2+ Zn

[0037] and one of organic ammonium. The organic ammonium includes but is not limited to tetrabutylammonium. 6 In certain embodiments, the Dawson-type heteropolyacid is selected from H 2 P 18 Mo 62 O 6 H 2 P 15 Mo 3 W 62 O 6 H 2 P 9 Mo 9 W 62 O 6 H 2 P 3 Mo 15 W 62 O 6 H 2 P 18 W 62 O 6 H 2 As 18 Mo 62 O 4 [Bu 5 N] 2 [S 18 W 62 O 8 TBA 2 [α-Si 18 W 62 O 19 [C 18 H 3 N 4 [S 2 Mo 18 O 62 [Bu 4N] 3 [Cl 2 W 18 O 62 and H 3 [V 2 W 18 O 62 , and at least one of H

[0038] According to another aspect of the present invention,

[0039] The Dawson type heteropolyacid is selected from (Bu 4 N) 4 [W 18 O 54 (SO 3 ) 2 , (TBA) 6 [H 3 W 18 O 56 (IO 6 )], and (NH 4 ) 9 [SbW 18 O 60 (OH) 2 , and at least one of them.

[0040] The Dawson type heteropolyacid and its salts may also include related isomers and derivatives. For example, they may be: α-H 6 P 2 Mo 18 O 62 , β-H 6 P 2 Mo 18 O 62 , α-H 6 P 2 W 18 O 62 , β-H 6 P 2 W 18 O 62 , [C 19 H 18 N 3 4 [α-S 2 Mo 18 O 62 , Na 16 (MnOH 2 ) 2 (Mn) 2 (P 2 W 15 O 56 ) 2 ​, Na 16 (MnOH 2 ) 2 (Mn) 2 (As 2 W 15 O 56 ) 2 , (Bu 4 N) 4 [W 18 O 54 (SO 3 ) 2 , (N(C 4 H 9 ) 4 ) 4 [(P 2 O 7 )Mo 18 O 54 , etc.

[0041] According to a specific embodiment of the present invention, the Dawson-type heteropolyacid is selected from H 6 P 2 Mo 15 W 3 O 62 , H 6 P 2 Mo 9 W 9 O 62 , H 6 P 2 Mo 3 W 15 O 62 . According to a preferred specific embodiment of the present invention, the Dawson-type heteropolyacid is H 6 P 2 Mo 9 W 9 O 62 .

[0042] In the present invention, the preparation of the Dawson-type heteropolyacid may include: dissolving the corresponding raw materials in a solvent and then mixing. After mixing, the pH value can be adjusted. The reagent for adjusting the pH value can be an acid reagent, a base reagent or a buffer solution, depending on the actual situation. The acid reagent can be strong acids such as hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ) and nitric acid (HNO 3 ); it can also be acetic acid (CH 3 COOH), phosphoric acid (H 3 PO 4 ). The base reagent can be sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonia water (NH3 ·H 2 O), trimethylamine (N(CH 3 ) 3 ) and pyridine (C 5 H 5 N), etc. The buffer reagent can be sodium bicarbonate buffer solution, phosphate buffer solution, acetate buffer solution, phosphate / dihydrogen phosphate buffer solution, mixed salt solution of potassium dihydrogen phosphate and disodium hydrogen phosphate, tris(hydroxymethyl)aminomethane / hydrochloric acid (Tris-HCl) buffer solution, potassium hydrogen phthalate solution, borax solution, etc. In the preparation of Dawson-type heteropolyacid, the reaction temperature can be 50 - 200 °C.

[0043] According to a specific embodiment of the present invention, sodium molybdate is added to deionized water to obtain a sodium molybdate solution. Sodium tungstate is added to deionized water to obtain a sodium tungstate solution. Disodium hydrogen phosphate is dissolved in deionized water to obtain a disodium hydrogen phosphate solution. Then the three solutions are mixed evenly to obtain a mixed solution. After heating the mixed solution to 50 - 100 °C, an acid solution is slowly added to adjust the pH value to 2 - 5. Then the mixed solution with adjusted pH value is reacted at 80 - 100 °C with stirring for 4 - 8 h. After the reaction is completed, the reaction solution is cooled to room temperature and extracted with ether, tetrahydrofuran or methyl tert-butyl ether. After removing the solvent, a solid product Dawson-type heteropolyacid is obtained.

[0044] According to another specific embodiment of the present invention, sodium molybdate and sodium tungstate are dissolved in deionized water (when dissolving, it is preferably heated, and the heating temperature can be 50 - 80 °C), then a certain amount of concentrated phosphoric acid is added dropwise, and then refluxed for 6 - 10 h. After the reaction solution is cooled, it is acidified with excessive hydrochloric acid and extracted with an equal volume of ether, tetrahydrofuran or methyl tert-butyl ether. After removing the solvent, a solid product Dawson-type heteropolyacid is obtained.

[0045] Among them, sodium molybdate, sodium tungstate, and disodium hydrogen phosphate can contain crystal water or can be anhydrous.

[0046] In the present invention, the reducing agent can be an organic reducing agent, an inorganic reducing agent or a composite reducing agent.

[0047] The organic reducing agent is glucose, fructose, sucrose, triose, pentose, maltose, sucrose, lactose, hydroquinone, vitamin C, coenzyme A, cysteine, a straight-chain or branched-chain alcohol, thioether or aldehyde having 2 to 30 carbon atoms. In certain specific embodiments, the organic reducing agent is selected from glucose, fructose, sucrose, triose, pentose, maltose, sucrose, lactose, hydroquinone, vitamin C, coenzyme A, cysteine, ethylene glycol, glycerol, dithioether, methylethyl dithioether, diethoxy dithioether, dimercapto diethyl sulfide, n-heptyl sulfide, benzyl sulfide, phenylbenzyl sulfide, 2-aminodiphenyl sulfide, amino sulfide, aminoethyl sulfide, thioanisole, amino thioanisole, polyphenylene sulfide, formaldehyde, acetaldehyde, propionaldehyde, isooctanal, nonanal, n-dodecanal, n-tetradecanal, 2,6-dimethylheptanal, α-methyldecanal, 2,6,10-trimethylundecanal, benzaldehyde, furfural, anisaldehyde, salicylaldehyde, glyceraldehyde.

[0048] The inorganic reducing agent is a reducing metal and its salt, thiourea, hydrazine (N 2 H 4 ). In certain specific embodiments, the reducing metal can be zinc, calcium, magnesium, aluminum, sodium, iron, and / or tin. The salt can be sodium sulfite, sodium thiosulfate, stannous chloride, sodium borohydride, calcium hydride, and / or lithium aluminum hydride.

[0049] The composite reducing agent is any one of the following: zinc and hydrochloric acid, zinc and acetic acid, iron and hydrochloric acid, tin and hydrochloric acid, sodium and ethanol, sodium and isopropanol.

[0050] In certain specific embodiments, the reducing agent can be: Al, Zn, B 2 H 6 , NaBH 4 , N 2 H 4 , NH 2 OH, SO 3 2- , S 2 O 4 2- , S 2 O 3 2- , SnCl 2 , MoCl 5 , MoOCl 5 2- , ascorbic acid (i.e., vitamin C), glucose, fructose, sucrose, triose, pentose, maltose, sucrose, lactose, thiourea, tartaric acid.

[0051] According to a specific embodiment of the present invention, the reducing agent is selected from one of vitamin C, glucose, and thiourea.

[0052] In the present invention, when coating the Dawson-type heteropoly blue solution, the solvent used in the Dawson-type heteropoly blue solution can be one or more of deionized water, methanol, ethanol, acetonitrile, ether, acetone, ethyl acetate, sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, isopropanol, butanol, toluene, xylene, chlorobenzene, dichlorobenzene, trichlorobenzene, anisole, methyl anisole, tetrahydrofuran, 2-methyltetrahydrofuran, N,N-dimethylformamide, diphenyl ether, N-methylpyrrolidone, γ-butyrolactone, and methoxyethylene glycol, preferably one of methanol, ethanol, isopropanol, acetonitrile, ether, acetone, and ethyl acetate, and more preferably methanol.

[0053] <Method for preparing anodic interface layer>

[0054] The present invention also provides a method for preparing an anodic interface layer as described above, comprising the following steps: 1) preparing a Dawson-type heteropoly acid solution; 2) preparing an alcohol solution of a reducing agent; 3) forming a Dawson-type heteropoly blue solution; 4) a coating step. Among them, steps 1) and 2) have no order. The following is a detailed description.

[0055] In step 1), the Dawson-type heteropoly acid is dissolved in a solvent (denoted as the first solvent), and the first solvent can be one or more of deionized water, methanol, ethanol, acetonitrile, ether, acetone, ethyl acetate, sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, isopropanol, butanol, toluene, xylene, chlorobenzene, dichlorobenzene, trichlorobenzene, anisole, methyl anisole, tetrahydrofuran, 2-methyltetrahydrofuran, N,N-dimethylformamide, diphenyl ether, N-methylpyrrolidone, γ-butyrolactone, and methoxyethylene glycol, preferably one of methanol, ethanol, acetonitrile, ether, acetone, and ethyl acetate, and more preferably methanol.

[0056] The preparation method of the Dawson-type heteropoly acid is referred to above and will not be elaborated here.

[0057] According to a specific embodiment of the present invention, the Dawson-type heteropoly acid is dissolved in an alcohol to obtain a Dawson-type heteropoly acid solution. The alcohol is selected from methanol, ethanol, or isopropanol, preferably methanol. The concentration of the heteropoly acid solution is 0.5 - 5 mg / mL, preferably 1 - 3 mg / mL, and more preferably 1 - 2 mg / mL. Heating may or may not be required during dissolution.

[0058] In step 2), the reducing agent is dissolved in a second solvent. The second solvent mentioned here can be one or more of deionized water, methanol, ethanol, acetonitrile, ether, acetone, ethyl acetate, sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, isopropanol, butanol, toluene, xylene, chlorobenzene, dichlorobenzene, trichlorobenzene, anisole, methylanisole, tetrahydrofuran, 2-methyltetrahydrofuran, N,N-dimethylformamide, diphenyl ether, N-methylpyrrolidone, γ-butyrolactone, and methoxyethylene glycol. Preferably, it is one of methanol, ethanol, acetonitrile, ether, acetone, and ethyl acetate, and more preferably methanol. The second solvent is preferably the same as the first solvent.

[0059] According to a specific embodiment of the present invention, the reducing agent is dissolved in an alcohol to obtain an alcohol solution of the reducing agent. The alcohol is selected from methanol, ethanol, or isopropanol, preferably methanol. The alcohol used in step 2) is the same as the alcohol used in step 1). The types of reducing agents used are as described above and will not be elaborated here. According to a preferred embodiment of the present invention, the reducing agent is selected from one of vitamin C, glucose, and thiourea. The concentration of the alcohol solution of the reducing agent can be 0.5 - 5 mg / mL, preferably 1 - 3 mg / mL, and more preferably 1 - 2 mg / mL.

[0060] In step 3), the Dawson-type heteropolyacid solution is mixed with the reducing agent solution and reacted to obtain a Dawson-type heteropolyblue solution. The molar ratio of the Dawson-type heteropolyacid in the Dawson-type heteropolyacid solution to the reducing agent in the reducing agent solution is between 1:0.05 and 1:20.

[0061] In step 4), the Dawson-type heteropolyblue solution is coated on the substrate to form an anodic interface layer. The solvents used in the Dawson-type heteropolyblue solution are as described above and will not be elaborated here.

[0062] The coating can be carried out by spin coating, blade coating, screen printing, slot die coating, spraying, inkjet printing, or rod coating.

[0063] The substrate is selected from glass, polyethylene terephthalate, and polyimide. The indium tin oxide glass sheet can be an indium tin oxide glass sheet treated with ultraviolet ozone.

[0064] According to a specific embodiment of the present invention, the Dawson-type heteropolyblue solution can be spin-coated onto an indium tin oxide glass sheet. During spin coating, the rotation speed is 2000 - 3500 rpm, preferably 2800 - 3300 rpm, and more preferably 3000 - 3200 rpm. The spin coating time can be 20 - 40 s, preferably 25 - 35 s, and more preferably 30 - 35 s.

[0065] The thickness of the Dawson-type heteropoly blue anode interface layer of the present invention can reach up to 1000 nm, preferably 10 nm to 500 nm, more preferably 10 nm to 150 nm, and can be, for example, 10 nm, 100 nm or 150 nm.

[0066] <Organic Solar Cell and Preparation Method>

[0067] According to one aspect of the present invention, the present invention provides an organic solar cell, comprising an anode, an anode interface layer, an active layer, a cathode interface layer and a cathode arranged in sequence, wherein the anode interface layer is the anode interface layer formed by coating with the Dawson-type heteropoly blue solution as described above. The Dawson-type heteropoly blue solution is the Dawson-type heteropoly blue solution as described above, which will not be elaborated herein.

[0068] In the present invention, the anode and the cathode can be selected from, but are not limited to, the following materials: ITO, FTO, AZO, aluminum, silver, gold, copper, calcium, magnesium, zinc, iron, platinum, silver nanowires, gold nanowires, copper nanowires, silver grids, copper grids, gold grids, graphene and PEDOT:PSS.

[0069] In the present invention, the active layer is composed of a donor material and an acceptor material, wherein the donor material can be selected from, but is not limited to, the following substances: a copolymer or a small molecule formed by coupling an electron-withdrawing conjugated unit and an electron-donating conjugated unit; the acceptor material can be selected from, but is not limited to, the following substances: fullerenes and their derivatives, perylene and its derivatives, naphthalene and its derivatives, fluorene and its derivatives.

[0070] The cathode interface layer can be selected from, but is not limited to, the following substances: calcium, magnesium, zinc, zinc oxide, titanium oxide, tin oxide, niobium oxide, zirconium oxide, lithium fluoride, cesium fluoride, cesium carbonate, lithium carbonate, sodium carbonate, polyfluorene and its derivatives, polyethylene diamine and its derivatives, BPhen and its derivatives, BCP and its derivatives, perylene and its derivatives, polyethylene oxide and its derivatives, polyvinyl pyrrolidone and its derivatives.

[0071] According to a specific embodiment of the present invention, the anode is ITO, the anode interface layer is the anode interface layer formed by coating with the Dawson-type heteropoly blue solution as described above, the active layer is formed by PM6 and L8-BO, the cathode interface layer is formed by PDINN, and the cathode is an Ag electrode or an Al electrode. Among them, the mass ratio of PM6 to L8-BO is 1:1.2 to 1.3. The thickness of the cathode is 90 to 220 nm.

[0072] In the present invention, PM6 has the following structure:

[0073]

[0074] Among them, 2-ethylhexyl is 2-ethylhexyl.

[0075] In the present invention, L8-BO has the structure as shown below:

[0076]

[0077] Among them, 2-butyloctyl is 2-butyloctyl.

[0078] In the present invention, PDINN has the structure as shown below:

[0079]

[0080] The present invention also provides a method for preparing a solar cell, which will be described in detail below.

[0081] According to a specific embodiment of the present invention, a Dawson-type heteropoly blue solution is spin-coated onto an indium tin oxide glass sheet treated with ultraviolet ozone, and without annealing, the ITO glass with a Dawson-type heteropoly blue anode interface layer is obtained. PM6 and L8-BO are mixed and dissolved in chloroform or dichloromethane, and DBCL (1,3-dibromo-5-chlorobenzene) is added, and stirred at 50-70 °C to obtain an active layer solution. The active layer solution is spin-coated onto the ITO glass covering the Dawson-type heteropoly blue anode interface layer and then annealed. After the temperature is cooled to room temperature, a PDINN cathode interface layer dissolved in a methanol solution is spin-coated on the active layer. Finally, an Ag electrode (i.e., the cathode) is evaporated under vacuum to obtain an organic solar cell device based on Dawson-type heteropoly blue.

[0082] In the present invention, the annealing conditions are as follows: the temperature is 100-400 °C, preferably 100-200 °C, more preferably 100-150 °C. The annealing time is 5-120 min, preferably 5-60 min, more preferably 5-20 min. The annealing can be carried out in an inert atmosphere.

[0083] <Application>

[0084] According to one aspect of the present invention, the present invention provides an application of Dawson-type heteropoly blue in forming an anode interface layer of an organic solar cell, and the Dawson-type heteropoly blue is obtained by reducing a Dawson-type heteropoly acid or its salt with a reducing agent. The Dawson-type heteropoly acid mentioned here is the Dawson-type heteropoly acid as described above, and the types of reducing agents used are referred to as above and will not be elaborated here.

[0085] According to another aspect of the present invention, the present invention also provides an application of Dawson-type heteropoly blue in forming a hole transport / injection layer of an organic light-emitting diode. The Dawson-type heteropoly blue is obtained by reducing a Dawson-type heteropoly acid or its salt with a reducing agent. The Dawson-type heteropoly acid mentioned here is the Dawson-type heteropoly acid as described above, which will not be elaborated here.

[0086] The present invention also provides an organic light-emitting diode, which includes an anode, a hole transport / injection layer, a light-emitting layer, an electron transport / injection layer, and a cathode arranged in sequence; the hole transport / injection layer is formed by coating a Dawson-type heteropoly blue solution, and the Dawson-type heteropoly blue is obtained by reducing a Dawson-type heteropoly acid or its salt with a reducing agent. The Dawson-type heteropoly acid mentioned here is the Dawson-type heteropoly acid as described above, and the Dawson-type heteropoly blue is the Dawson-type heteropoly blue as described above, which will not be elaborated here.

[0087] In the present invention, the light-emitting layer is composed of a host material and a guest material. The host material can be selected optionally, but is not limited to the following substances: 4,4'-bis(9-carbazolyl)biphenyl (CBP), 4,4',4''-tris(carbazol-9-yl)triphenylamine (TCTA), 9,9'-(1,3-phenylene)di-9H-carbazole (mCP), poly(9,9-dioctylfluorene-2,7-diyl) (PFO) and its derivatives; the guest material can be selected optionally but is not limited to the following substances: Ir(MDQ)2(acac), Ir(ppy)3, Ir(ppy)2(acac), Ir(mppy)3, FIrpic, Ir(piq)2acac.

[0088] The following introduces the test method:

[0089] Infrared spectrum determination: Use a Perkin Elmer Spectrum 400 series Fourier transform infrared-near infrared spectrometer.

[0090] Ultraviolet-visible absorption spectrum: Use a Hitachi ultraviolet-visible spectrophotometer U-2910 for ultraviolet-visible absorption spectrum measurement.

[0091] Preparation Example 1

[0092] Prepare Dawson-type heteropoly acid H 6 P 2 Mo 9 W 9 O 62 。

[0093] Dissolve 10.89 g of sodium molybdate dihydrate and 14.84 g of sodium tungstate dihydrate in 36 mL of hot deionized water (50 °C), add dropwise 25 mL of concentrated phosphoric acid, and heat under reflux at 120 °C for 8 h. After the reaction solution is cooled, acidify it with excessive hydrochloric acid, extract it with an equal volume of diethyl ether, and volatilize the diethyl ether at room temperature to obtain the solid product Dawson-type heteropolyacid H 6 P 2 Mo 9 W 9 O 62 . Dissolve the obtained Dawson-type heteropolyacid in methanol to prepare a Dawson-type heteropolyacid solution with a concentration of 0.5 mg / mL.

[0094] Preparation Example 2

[0095] Preparation of Dawson-type heteropolyacid H 6 P 2 Mo 3 W 15 O 62 . The difference from Preparation Example 1 is that only the feed ratio is changed, and the other operations are the same as those in Preparation Example 1.

[0096] Preparation Example 3

[0097] Preparation of Dawson-type heteropolyacid H 6 P 2 Mo 15 W 3 O 62 . The difference from Preparation Example 1 is that only the feed ratio is changed, and the other operations are the same as those in Preparation Example 1.

[0098] Example 1

[0099] Dissolve vitamin C in methanol to prepare a methanol solution of vitamin C with a concentration of 0.5 mg / mL. Mix 1 mL of the Dawson-type heteropolyacid solution prepared in Preparation Example 1 with 1 mL of the methanol solution of vitamin C, stir at room temperature to obtain a Dawson-type heteropolyan blue solution. Spin-coat the Dawson-type heteropolyan blue solution onto an indium tin oxide glass sheet treated with ultraviolet ozone. During spin-coating, the rotation speed is 3000 rpm for 30 s. Without annealing, the ITO glass covered with the Dawson-type heteropolyan blue anode interface layer is obtained.

[0100] Example 2

[0101] The difference from Example 1 is only that anhydrous glucose is used to replace vitamin C in Example 1. The other operations are the same as those in Example 1. The ITO glass covered with the Dawson-type heteropolyan blue anode interface layer is obtained.

[0102] Example 3

[0103] The difference from Example 1 is only that thiourea is used to replace vitamin C in Example 1. The remaining operations are the same as those in Example 1. ITO glass covered with a Dawson-type heteropolytungstate blue anode interface layer is obtained.

[0104] Comparative Example 1

[0105] The Dawson-type heteropolyacid solution obtained in Preparation Example 1 was spin-coated onto an indium tin oxide glass sheet treated with ultraviolet ozone. During spin-coating, the rotation speed was 3000 rpm and the time was 30 s. Annealing was carried out at 100 °C for 10 min. ITO glass covered with a Dawson-type heteropolyacid anode interface layer was obtained.

[0106] Experimental Example

[0107] (I). Infrared spectrum

[0108] The Dawson-type heteropolyacids prepared in Preparation Example 1, Preparation Example 2 and Preparation Example 3 were subjected to infrared spectrum measurement.

[0109] The Dawson-type heteropolyacids prepared in Preparation Example 1, Preparation Example 2 and Preparation Example 3 were uniformly mixed with KBr powder at a ratio of 1:200 respectively, and thin film samples with KBr pellet substrates were prepared by the pellet pressing method. The transmittance was measured using a Fourier transform infrared spectrometer. Their infrared spectra are shown in Figure 1 , and it can be seen that they have the same Dawson structure, and the infrared spectra of these three compounds are similar. Taking H 6 P 2 Mo 15 W 3 O 62 as an example, the infrared spectrum in the fingerprint region shows four bands at 1065 cm -1 , 965 m -1 , 865 cm -1 , 786 cm -1 . The absorption bands in the fingerprint region show the characteristics of the Dawson-type structure.

[0110] (II). Ultraviolet-visible absorption spectrum

[0111] The Dawson-type heteropolyacid solutions prepared in Preparation Example 1, Preparation Example 2 and Preparation Example 3 were spin-coated onto quartz wafers respectively to prepare solid thin films. Their absorption spectra were measured using an ultraviolet-visible absorption spectrometer and are shown in Figure 2 . It can be seen that they all have strong absorption in the range of 250 - 400 nm. The absorption band is caused by the charge transfer transition from bridging oxygen to metal atoms. At the same time, there is no absorption in the visible light region, indicating that H 6 P2 Mo 3 W 15 O 62 、H 6 P 2 Mo 9 W 9 O 62 and H 6 P 2 Mo 15 W 3 O 62 are all suitable as interfacial layer materials in the spectrum.

[0112] (III) Preparation and Performance Testing of Organic Solar Cell Devices

[0113] 1. Use the ITO glass covered with the Dawson-type heteropolyacid anode interfacial layer of Comparative Example 1.

[0114] Dissolve 2 mg of PM6 and 2.4 mg of L8-BO in 250 μL of chloroform, add 3 mg of DBCL (1,3-dibromo-5-chlorobenzene), and stir at 60 °C for 1.5 h to prepare an active layer solution. Then spin-coat the active layer solution onto the ITO glass covered with the heteropolyacid anode interfacial layer and anneal at 100 °C for 10 min. After the temperature cools to room temperature, spin-coat a 1 mg / ml PDINN cathode interfacial layer dissolved in methanol solution on the active layer at a rotation speed of 3000 rpm for 30 s. Finally, evaporate an Ag electrode with a thickness of 100 nm under 3×10 -5 Pa to obtain an organic solar cell device based on Dawson-type heteropolyacid. The structure of the organic solar cell device is (indium tin oxide ITO / anode interfacial layer / active layer / cathode interfacial layer / Ag electrode), where the thickness of the anode interfacial layer is about 10 nm, the thickness of the active layer is about 100 nm, and the thickness of the cathode interfacial layer is about 10 nm.

[0115] In a glove box filled with nitrogen, use an AAA-class solar simulator AM 1.5G to test the current-voltage curve of the prepared solar cell at an intensity of 100 mW / cm 2 . The above solar simulator is calibrated using a silicon cell certified by Newport Corporation, USA.

[0116] Based on the H synthesized in Comparative Example 1 6 P 2 Mo 9 W 9 O 62 The test results of the organic solar cell are as shown in the curve in Figure 3 , and its open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency are 0.883 V, 25.819 mA / cm 2, 0.737, 16.805%.

[0117] Based on the conductivity test results of the synthesized H measured at a bias voltage of 0.3V in Comparative Example 1 6 P 2 Mo 9 W 9 O 62 are shown as curve a in Figure 4 , and its conductivity is 8.55×10 -4 S / m.

[0118] 2. ITO glasses covered with Dawson-type heteropoly blue anode interface layers of Example 1, Example 2, and Example 3 were used respectively.

[0119] Referring to the operation of Comparative Example 1, an active layer, a cathode interface layer, and a cathode were successively prepared on the ITO glass covered with the Dawson-type heteropoly blue anode interface layer of Example 1, and then the photovoltaic performance was tested. The open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency results are shown in Figure 5 and Table 1. The conductivity results measured at a bias voltage of 0.3V are shown in Table 1 and Figure 4 curve b in

[0120] Referring to the operation of Comparative Example 1, an active layer, a cathode interface layer, and a cathode were successively prepared on the ITO glass covered with the Dawson-type heteropoly blue anode interface layer of Example 2, and then the photovoltaic performance was tested. The open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency results are shown in Table 1 and Figure 6 . The conductivity results measured at a bias voltage of 0.3V are shown in Table 1 and Figure 4 curve c in

[0121] Referring to the operation of Comparative Example 1, an active layer, a cathode interface layer, and a cathode were successively prepared on the ITO glass covered with the Dawson-type heteropoly blue anode interface layer of Example 3, and then the photovoltaic performance was tested. The open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency results are shown in Table 1 and Figure 7 . The conductivity results measured at a bias voltage of 0.3V are shown in Table 1 and Figure 4 curve d in

[0122] Table 1

[0123]

[0124] As can be seen from the table, compared with Comparative Example 1, the conductivity of the organic solar cell device fabricated by using the anode interface layer formed by Dawson-type heteropoly blue in the present invention is significantly improved. In addition, the photoelectric conversion efficiency and the fill factor are also increased. This should be attributed to the improved conductivity of the anode interface layer formed by heteropoly blue.

[0125] The present invention is not limited to the above embodiments, and any variations, improvements, and substitutions that can be conceived by those skilled in the art without departing from the essence of the present invention fall within the scope of the present invention.

Claims

1. An anode interface layer for an organic solar cell, characterized in that: The method is formed by coating a Dawson type heteropoly blue solution, wherein the Dawson type heteropoly blue in the Dawson type heteropoly blue solution is obtained by reducing a Dawson type heteropoly acid or a salt thereof with a reducing agent.

2. The anode interface layer according to claim 1, characterized in that: The general formula of the Dawson type heteropoly acid is Y n [X2M 18 O 62 ]; Wherein, X is selected from one of P, As, S, Si, Cl and V, M is selected from at least one of W and Mo, n is the molar coefficient of Y, n is greater than or equal to 6 and less than or equal to 12; Y is selected from H + , Li + 、Ag + , Cu + , K + 、Na + NH4 + Mg 2+ , Ca 2+ , Sr 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ and one of the organic ammoniums.

3. The anode interface layer according to claim 1, characterized in that: Dawson type heteropolyacid is selected from (Bu4N)4[W 18 O 54 (SO3)2]、(TBA)6[H3W 18 O 56 (IO6)] and (NH4)9[SbW 18 O 60 (OH)2] at least one.

4. The anode interface layer according to claim 1, characterized in that: The Dawson type heteropoly acid is selected from H6P2Mo 15 W3O 62 、H6P2Mo9W9O 62 and H6P2Mo3W 15 O 62 At least one of; The reducing agent is selected from one of vitamin C, glucose and thiourea.

5. A method for preparing an anode interface layer according to claim 1, characterized in that: The following steps are involved: dissolving a Dawson type heteropoly acid in a solvent to obtain a heteropoly acid solution; The heteropoly acid solution and the reducing agent solution are mixed and reacted to obtain a Dawson type heteropoly blue solution; the Dawson type heteropoly blue solution is coated on a substrate to form an anode interface layer.

6. A use of a Dawson type heteropoly blue in forming an anode interface layer of an organic solar cell, characterized in that: The Dawson type heteropoly blue is obtained by reducing a Dawson type heteropoly acid or a salt thereof with a reducing agent; the Dawson type heteropoly blue solution is coated to form an anode interface layer.

7. An organic solar cell comprising an anode, an anode interface layer, an active layer, a cathode interface layer and a cathode arranged in sequence, characterized in that: The anode interface layer is formed by the anode interface layer according to claim 1.

8. The organic solar cell according to claim 7, characterized in that The anode is ITO, the active layer is formed by PM6 and L8-BO, the cathode interface layer is formed by PDINN, and the cathode is an Ag electrode or an Al electrode.

9. A use of a Dawson type heteropoly blue in forming a hole transport / injection layer of an organic light emitting diode, characterized in that: The Dawson type heteropoly blue is obtained by reducing a Dawson type heteropoly acid or a salt thereof with a reducing agent; a Dawson type heteropoly blue solution is coated to form a hole transport layer.

10. An organic light emitting diode, comprising an anode, a hole transport / injection layer, a light emitting layer, an electron transport / injection layer and a cathode arranged in sequence; characterized in that: The hole transport / injection layer is formed by coating a Dawson type heteropoly blue solution, and the Dawson type heteropoly blue is obtained by reducing a Dawson type heteropoly acid or a salt thereof with a reducing agent.

Citation Information

Patent Citations

  • Polymer solar cell

    CN103280528A

  • Organic solar cell based on heteropoly acid anode modifying layer and preparation method of organic solar cell

    CN103400941A

  • Process for preparing pure heteropolyblue

    CN1623904A